Tests of quantum gravity in the laboratory - Lustosa, Francisco Bento (Cadernos de Astronomia, 2025)
This work introduces some of the main topics related to recent efforts to conduct experiments that prove the quantum nature of gravity in the laboratory. An overview of the conceptual problems involved will be presented, describing the most well-known theories as well as discussing some of the most relevant approaches for laboratory experiments, such as the Diósi-Penrose decoherence model. Using the formalism of canonical quantization of linearized gravity, it is demonstrated how predictions are beginning to be extracted from the known theories for a regime that is still little explored experimentally. Next, some of the main experimental proposals in the literature are discussed, particularly the possibility of generating entanglement between two massive sources in a state of quantum superposition and the tests involving optomechanical systems. The conclusions list open problems related to traditional methods of gravity quantization in the low-energy regime and discuss the most promising experimental paths to test predictions that could confirm the quantum nature of the gravitational field.